Students' Anxiety in Reading Aloud at MTs Negeri 3 Bolaang Mongondow Timur-Sulawesi Utara - Muhamad Riski Mokoginta; Nur Halimah; Lies Kryati (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
Students' Anxiety in Reading Aloud at MTs Negeri 3 Bolaang Mongondow Timur was a study that aimed to find out what factors influence students anxiety in reading aloud. This study employed descriptive qualitative method with a qualitative approach. The participants were 15 students in VIII-1 class of MTs Negeri 3 Bolaang Mongondow Timur-Sulawesi Utara. Furthermore, the data was analysed and portrayed into charts, then discussed with existed theories. The result of the research revealed some factors that make students feel anxious in reading aloud. First, personal factors caused students felt anxious such as worry about reading effects and afraid of making an error. Second, the text features also influenced the anxiety in reading aloud such as unfamiliar culture, unfamiliar topic, and unknown vocabulary. By understanding the result, it suggested to the teacher to implement several ways to minimize the students’ anxiety such as determining the times of reading aloud, encouraging the students to learn while reading and providing feedback in illustrating language learnt, using text talk, print referencing, and previewing.  As a result, this study contributes to the improvement of techniques that the teacher used in conducting reading aloud activity to reduce the students’ anxiety.Keywords:     Anxiety, Reading Aloud